Entry into A Cardiac Surgery Set Up: The Associated Risks and Difficulties for Inexperienced New Medical Staff - Nazmul Hosain,; Aniqa Sattar,; Maruf Hassan Alam Arnob,; Md Anisuzzaman,; Chowdhury, Md Abdul Quaium (Cardiovascular Journal, 2024)
Background: Cardiac Surgery is one of the most sophisticated branches of medical science, which is continually being updated. With very little inclusion in medical course curriculum, medical graduates have limited orientation of this pristine subject. Capacity building is lengthy and cardiac surgery units often contain unrelated junior doctors due to scarcity of cardiac surgeons. New residents may also face similar difficulties. The objectives of this article are to describe the difficulties faces by newly posted doctors and offer some solutions. Methods: This study was conducted in the Department of Cardiac Surgery, Chittagong Medical College & Hospital (CMCH) between January 2020 and December 2022. A confidential self-report system questionnaire was used to interview 30 newcomers in CMCH and other cardiac surgery set ups and their findings are compiled in the article. Results: The interviewed doctors and residents have described individualities of cardiac surgery department and the difficulties they faced while working here. They also offered some solutions of the problems faced by them. Conclusion: Cardiac surgery is a stressful job. The new residents and unrelated doctors face various problems while beginning here. This is more troublesome for the female doctors, but doctors trained in cardiology or other surgical disciplines suffered least. Orientation initiatives by the cardiac surgery department and publishing a complete manual handbook to provide guidelines will be helpful in this regard. Cardiovasc j 2024; 16(2): 81-85